Conséquences des changements climatiques en milieu océanique - Grégory Beaugrand; Eric Goberville (VertigO)
Climate change is unambiguous and its effects are clearly detected in all functional units of the Earth System. This paper presents analyses of sea surface temperature and show that climate change is affecting both biological and ecological systems of the world and most specifically the North Atlantic and its adjacent seas. Changes are seen from phytoplankton to zooplankton to fish and are modifying the dominance of species and the structure, the diversity and the functioning of marine ecosystems. Changes also range from biogeographical to phenological shifts and have involved in some regions of the Atlantic abrupt ecosystem shifts also called regime shifts. These alterations reflect the response of ecosystems to a warmer temperature regime. Mechanisms are complex because they are nonlinear exhibiting tipping points and varying in space and time. Sensitivity of organisms to temperature changes is high, implicating that a small modification in the temperature regime can have sustained ecosystem effects. It is urgent to develop monitoring systems, indicators and both statistical and mathematical tools to detect, better understand and anticipate the alterations of both biological and ecological systems that may be triggered by global climate change.